Trends in intentional and unintentional events among paediatric patients at a tertiary care center in Gandaki Province, Nepal - KC, Namrata; Panjiyar, Aman; Shrestha, Bandana; Shretha, Nirmala; Hirachan, Neelu; Timasina, Ravi (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: The poisoning and paediatric medicolegal cases among children have been a major cause of hospital admission and a significant global health problem, including Nepal. Unintentional event like poisoning is common among infants and younger children, whereas in older children, poisoning is usually intentional. The aim of this study was to find out the trends in the Intentional and Non-intentional events among paediatric cases admitted to a tertiary care center. Methods: The hospital records of children admitted in Paediatric Intensive Care Unit (PICU) of tertiary care center, Gandaki Province, Nepal from April 2020 to March 2024 were analysed. After ethical approval from Institutional Review Committee, hospital files of 105 patients were conveniently chosen for analysis. The data were analysed using SPSS version 25.0. Results: Among 105 admitted cases, 53(50.48%) were males and 52(49.52%) were females. The median (interquartile range-IQR) age was 4.5 years (IQR=2-12 years). Seventy-four percent of cases had unintentional events. Pesticides were the common ingestion source for both unintentional and intentional events. Interpersonal issues being the common reason (70.83%) of intentional event. The likelihood of intentional event was 11.2 times more among females than male participants (Crude odd ratio: 11.29; 95% CI: 3.10-41.01; p< 0.001). The median (interquartile range) of age for intentional event: 14(13-15) was significantly higher than unintentional event: 3(2-6), p<0.001. Conclusions: The unintentional events were common in younger children and intentional events among older children and pesticides being the most common poisoning, highlighting the need of control of availability of toxic pesticides, education regarding safety storage and mental health education for adolescence.